"An Be Jigi": Collective cooking, whole grains, and technology transfer in Mali - Wenda K. Bauchspies; Fatimata Diarra; Fred Rattunde; Eva Weltzien (Canadian Science Publishing, 2017)
This paper addresses how available resources, food security, technology, and culture are shaping the choices rural Malian women are making to ensure the health, energy, and well-being of their families. This research contributed to evaluating an eight-year research project (An Be Jigi) targeting improved nutrition. The study, performed over four months, used semi-structured interviews of 120 women in six villages in Mali to assess the identified issues with qualitative and quantitative approaches. This paper describes the history of the An Be Jigi project, whole-grain processing techniques, and group cooking for knowledge sharing with rural women for improved nutrition. Interviews revealed substantial adoption of whole-grain processing techniques and women's appreciation of the nutritional benefits of those techniques. The women engaged in group cooking (cuisines collectives) appreciated the activities and mentioned multiple benefits from using them. Women identified access to mills, and to some extent the social stigma of laziness and poverty associated with whole-grain food, as limiting factors of adoption. This study of women's practices and perceptions regarding use of whole grain tells a story of changing consumption habits being shaped by culture, technology, knowledge, and available resources. Malian women are agents of change and care in their adoption of new techniques and recipes for the improved nutrition of young children and households. If science is not crafted to address the local character of farming places and practices, then growers are unlikely to accept the research-based advice of advisors. -Henke (2000, p. 485)